Total Phenol and Antioxidant Activity of Ethanol Extract and Water Extract from Claw Uncariaa gambir Roxb - Hartanti, Lucky; Ashari, Asri Mulya; Warsidah, Warsidah (Universitas Jember, 2021)
Uncaria gambier Roxb is a plant from the Rubiaceae family, belongs to the Bajakah group and has been used empirically in the treatment of various types of diseases in the community. Besides being one of the industrial plants and export commodities produced in Sumatra and Kalimantan, gambier leaves is also used frequently in Indonesia, both for the pharmaceutical and cosmetic industries. As a result, market demand both nationally and internationally have increased. The aim of this research are determination of antioxidant activity of ethanol extract and aqueous extract of gambir claw using 1,1-diphenil-2-picrylhydrazyl (DPPH) and determination of total phenol using Calcetau folin reagent. Gambier plant samples were taken in the forest area around the Tanjungpura University campus, the claws were separated and dried at room temperature, then powdered and extracted by maceration using 70% ethanol pa and aquadest, then the extract was concentrated until it was ready to be tested for antioxidant activity and determination of total phenol. The total phenolic ethanol extract and aqueous extract of gambir claw were 224.66 mg GAE/g extract (GEA : Gallic Acid Eqivalent) and 299.08 mg GAE/g extract, respectively, while the antioxidant potential (IC50) was 39.566 μg/mL and 65.140 μg/mL, and the IC50 for comparison of Vitamin C was 7.02 μg/mL.